Ethnobotany of Acrocomia aculeata (Jacq.) Lodd. ex Mart. in two ecoregions of Colombia - Gonzalez, Danna Carolina; Tranbarger, Timothy J.; Isaza, Carolina (Ethnobotany Research and Applications, 2025)
Background: Acrocomia aculeata is a multipurpose neotropical palm, widely distributed in Colombia with a large potential in the oil and food sector. However, its management and uses in the country are largely unknown. Therefore, the current study involves an ethnobotanical study on the use, management, and commercialization of Acrocomia aculeata in two regions of Colombia, where wild populations are found. Materials and Methods: Participant and non-participant observation sessions were conducted, along with semi-structured interviews with traders, processors, and consumers of palm, in 10 municipalities of Santander and Casanare, exploring harvesting methods, market characteristics, and uses of the palm. Results: In Casanare, nine categories were identified, while seven were noted in Santander, with human and animal food being the most prominent in both regions. In Casanare, buds and fruits are harvested, whereas in Santander, only the fruits are collected. Processing is done using traditional artisanal methods, and the market is incipient and seasonal across the two regions. In Casanare, the market is characterized by the offer of handicrafts and utilitarian objects (rings, fans, brooms, and hats), while in Santander, comprises food products derived from the fruit (fruits, chicha, and ice cream). However, a decline in usage was attributed to the depletion of the resource. Conclusions: The study outlines the use and commercialization of Acrocomia aculeata in Casanare and Santander, highlighting its cultural, social, and economic significance. Despite its considerable commercial potential, it is crucial to address the challenges related to use decline and resource depletion. Keywords: Corozo, commerce, management, traditional uses, local knowledge